Ocena sestojne zgradbe na območju Krakovskega pragozdnega rezervata s segmentacijo podatkov laserskega skeniranja - Hladnik, David (Gozdarski vestnik, 2017)
In Krakovo virgin forest reserve we assessed stand structures on the basis of the laser scanning data of Slovenia and forest inventory permanent sampling plots. Large growing stocks (730 m3 /ha) and quantities of deadwood (27 % of growing stock) are characteristic for a reserve in the area of lowland, occasionally flooded forests. Pedunculate oak (83 %) and common hornbeam (12 %) prevail in the growing stock. We delineated stand structures in the forest reserve zone on the basis of the height difference using the procedure of the lidar data segmentation. On the digital model of tree crowns in the canopy of the central stand with the pedunculate oak in the upper level we determined only two unfilled gaps, larger than 100 m2 . In the neighboring managed forest, we classified the stands according to four-meter height classes from the height of 16 m to the heights of stand canopy over 32 m. Superficial forest stands% diversity was assessed using the spatial model, where the stands and stand subunits, larger than a quarter of a hectare, are presented.
Keywords: forest reserve; gozdni rezervati; sestojne strukture; stand structures; Krakov; laser scanning of Slovenia; lasersko skeniranje Slovenije